Radiative Heat and Mass Transfer of an MHD Free Convection Flow Along a Stretching Sheet with Chemical Reaction, Heat Generation and Viscous Dissipation (Dhaka University Journal of Science, 2013)
In the present study, an analysis is carried out to investigate the effect of chemical reaction and radiation on a steady two-dimensional magneto-hydrodynamics (MHD) heat and mass transfer free convection flow of a viscous incompressible fluid along a stretching sheet with heat generation along with the effect of viscous dissipation. The basic non-linear partial differential equations governing the flow field are reduced to a system of coupled non-linear ordinary differential equations by similarity transformations and the equations are solved numerically by applying Nachtsheim-Swigert shooting iteration technique along with sixth order Runge-Kutta integration scheme. The numerical results with respect to embedded parameters are displayed graphically for the non-dimensional velocity, temperature and concentration profiles. Finally the effects of the pertinent parameters which are of physical and engineering interest are presented in tabular form. Dhaka Univ. J. Sci. 61(1): 27-34, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15092